2017
DOI: 10.1021/acs.bioconjchem.7b00682
|View full text |Cite
|
Sign up to set email alerts
|

DNA Hybridization Assay Using Gold Nanoparticles and Electrophoresis Separation Provides 1 pM Sensitivity

Abstract: The efficiency of gold nanoparticle (AuNP) dimerization mediated by hybridization between two probe DNA molecules and a complementary target DNA molecule was maximized by examining several possible hybridization combinations. The uniformity of the size of the AuNPs, the use of surface modification appropriate for high hybridization efficiency, together with efficient blocking of nonspecific binding, all contributed to achieving a 1 pM detection limit following conventional gel electrophoresis separation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…When the surfaces of colloids are modified with biomolecules such as proteins, their colloidal behaviors are highly complicated, mainly due to the fact that intrinsic properties of the surface-bound molecules greatly affect the colloidal stability. For example, DNA-functionalized particles, including microbeads, gold nanoparticles, silver nanoparticles, and quantum dots are readily aggregated by using DNA duplex formation in a cross-linking manner. Both turbidity changes and solution color changes induced by colloidal aggregation allow the naked-eye detection of DNA duplex formation. Therefore, such particles can be used as a powerful tool in medical diagnosis. Moreover, careful design of base sequence of surface-grafted DNA can afford colloidal crystals and nanoparticle superlattices, both of which are potentially applicable to various devices.…”
Section: Introductionmentioning
confidence: 99%
“…When the surfaces of colloids are modified with biomolecules such as proteins, their colloidal behaviors are highly complicated, mainly due to the fact that intrinsic properties of the surface-bound molecules greatly affect the colloidal stability. For example, DNA-functionalized particles, including microbeads, gold nanoparticles, silver nanoparticles, and quantum dots are readily aggregated by using DNA duplex formation in a cross-linking manner. Both turbidity changes and solution color changes induced by colloidal aggregation allow the naked-eye detection of DNA duplex formation. Therefore, such particles can be used as a powerful tool in medical diagnosis. Moreover, careful design of base sequence of surface-grafted DNA can afford colloidal crystals and nanoparticle superlattices, both of which are potentially applicable to various devices.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Previous study has shown that the alkanethiol modication enhanced the dispersion stability of AuNPs. [24][25][26] We successfully made MCH-modied ssDNA-AuNPs with lower amount of the immobilized ssDNA that showed the same salt stability as MCH-free ssDNA-AuNPs with higher amount of the immobilized ssDNA. Since the detection sensitivity was better for the former ssDNA-AuNPs, our results suggest that the amount of immobilized ssDNA is important for the efficient detection.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, there are many examples of sandwich hybridization protocols based on the use of highly sensitive radioactive probes or gold or fluorescent nanoparticles. The latter ones are preferred to the radioactive probes for obvious safety reasons, although they are less sensitive . Hence, the development of highly sensitive fluorescence-based methods for ctDNA detection may be attractive but challenging.…”
Section: Introductionmentioning
confidence: 99%